Preparation method for chemically plating silver on surface of hafnium cyanide powder
Through the method of sensitization activation such as NaF and HF coarsing, PbCl2 and other sensitization activation combined with electroless silver plating, the problem of insufficient surfactivity of HfCxNy powder is solved, and a uniform silver plating is achieved, which improves oxidation resistance and wettability, and expands the application of HfCxNy ceramics.
Patent Information
- Application Number
- CN202510526964.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-25
- Publication Date
- 2025-07-18
AI Technical Summary
HfCxNy powder has low surface activity, insufficient oxidation resistance, and there is a lack of effective electroless silver plating method in the prior art.
The crude liquid composed of NaF and HF is used for roughening treatment, and combined with the sensitization activation liquid composed of PbCl2, HCl, SnCl2·2H2O and NaCl for sensitization and activation. Then, electroless silver plating is carried out under specific conditions to control the concentration and temperature of the silver solution and reducing agent to ensure uniform distribution of silver ions and continuity of the plating layer.
A uniform and dense silver coating is formed on the surface of HfCxNy powder, which improves oxidation resistance and wettability with metals, realizes the HfCxNy~Ag core-shell structure, and expands the application range of HfCxNy ceramics.
Smart Images

Figure CN120330690A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the fields of materials science and surface engineering, and relates to a preparation method for electroless silver plating on the surface of hafnium carbonitride (HfC x N y ) powder. Technical Background
[0002] In recent decades, there has been an increasing interest in ultra-high temperature ceramics as potential materials for hypersonic applications, and HfC x N y as a new ultra-high temperature material has potential application value in high-temperature fields such as turbine blades in the aerospace field, the manufacture of aircraft gas turbines, power plants of steam turbines, and rocket engines due to its ultra-high melting point and excellent ablation resistance. However, HfC x N y powder materials still have some limitations in practical applications. For example, their oxidation resistance is insufficient, and brittle HfO2 will form on the surface; as a powder reinforcement component, their wettability with metals is poor, and surface coating is required.
[0003] Ag is a soft metal, which can not only act as a reinforcement phase but also play an important role as a lubricating phase. Compared with Ni and Cu phases, the Ag phase can reduce the friction coefficient when sliding with metals. Currently, common silver plating methods include electroless silver plating. For example, patent CN101012552A involves a stable and replenishable fiber electroless silver plating method, and the techniques adopted include the following processes: (1) performing degreasing, roughening, and sensitization pretreatment on the fiber; (2) electroless silver plating; (3) replenishing and adjusting the electroless silver plating solution for reuse. In the actual application of this technique, hydrochloric acid, sulfuric acid, sodium hydroxide, ammonium sulfate, etc. are generally used as roughening agents. During sensitization, a mixed liquid composed of stannous chloride and hydrochloric acid is generally used as a sensitizer, and the activation solution used is composed of silver nitrate and ethylenediaminetetraacetic acid or its salts. At the same time, the fibers involved are of organic material.
[0004] After retrieval, it is found that so far, there have been few reports on the technique of electroless silver plating on the surface of HfCxNy powder. Summary of the Invention
[0005] The purpose of the present invention is to provide a method for electroless silver plating on the surface of ultra-high temperature HfC x N y powder to solve the problems such as low surface activity and insufficient oxidation resistance of HfC x N y powder.
[0006] The present invention also realizes for the first time the uniform plating of a large proportion of Ag on the surface of HfC x N y powder.
[0007] The present invention provides the following technical solutions:
[0008] A preparation method for electroless silver plating on the surface of hafnium cyanide powder; comprising the following steps:
[0009] 1) Pretreatment: The raw material powder is successively subjected to coarsening, sensitization + activation, and drying; the raw material powder is hafnium cyanide powder, and the chemical formula of the hafnium cyanide powder is: HfC x N y ;
[0010] The coarsening is: adding hafnium cyanide powder to the coarsening solution, ultrasonically treating at room temperature, then standing until the powder settles, and then washing with deionized water; the coarsening solution is composed of NaF and HF, wherein the concentration of NaF is 3 - 6 g / L, and in the coarsening solution, the concentration of HF is 1 - 3 mol / L;
[0011] The sensitization + activation is: adding the coarsened hafnium cyanide powder to the treatment solution; synchronously performing sensitization and activation treatment under ultrasonic wave action for at least 10 min, standing until the powder settles, and rinsing with deionized water; the treatment solution is composed of PbCl2, HCl, SnCl, and NaCl; wherein the concentration of PbCl2 is 0.4 - 0.6 g / L, the concentration of HCl is 0.5 - 1.0 mol / L, the concentration of SnCl·2H2O is 25 - 35 g / L, and the concentration of NaCl is 150 - 170 g / L;
[0012] 2) Electroless plating: adding the pretreated and dried hafnium cyanide powder to the reducing solution, and then adding the silver-containing solution to the reducing solution, stirring evenly to obtain the electroless silver plating solution; at a temperature of 30°C - 50°C, preferably 30 - 40°C, and further preferably 30 - 35°C, stirring the electroless plating solution for electroless plating, and after the electroless plating is completed, washing, filtering, and drying the powder to obtain silver-plated hafnium cyanide composite particles; in the electroless silver plating solution, the concentration of silver nitrate is 25 - 40 g / L of AgNO3, the concentration of ammonia water is 2.5 - 3.5 mol / L, the concentration of formaldehyde HCHO is 0.3 - 0.35 mol / L, and the concentration of ethanol is 10 - 11.5 mol / L; and the amount of ethanol used in the electroless silver plating solution is greater than the amount of water used; the pH of the electroless silver plating solution is 11 - 12;
[0013] During electroless plating, the stirring speed is 750 r / min - 1000 r / min.
[0014] In the present invention, sensitization and activation are combined together, simplifying the pretreatment process. Coarsening is carried out using a special coarsening agent to make HfC x N yNumerous tiny concave surfaces are formed on the powder surface, which is beneficial to the adsorption of precious metal ions at this place and facilitates the subsequent electroless plating. Sensitization and activation further enhance the adhesion ability of the plating solution on the powder surface and improve the surface activity of HfC x N y powder. By changing factors such as the pre-treatment process of HfC x N y powder before plating, the concentration of AgNO3, the electroless plating temperature, and the pH value, etc., the present invention realizes the regulation of the microstructure and morphology of the composite particles, and prepares HfC x N y ~Ag core~shell structure composite particles.
[0015] Preferably, the particle size of the raw material powder is 8-10 microns.
[0016] Preferably, during roughening, hafnium cyanide powder is added to the roughening solution, ultrasonicated at room temperature for 10-20 min, then left to stand until the powder settles, and then the powder is washed with deionized water at least 2 times; in the roughening solution, the concentration of NaF is 3.5-4.5 g / L, and the concentration of HF is 1.5-2.5 mol / L. During roughening, the liquid-solid ratio is greater than or equal to 4:1, preferably 4-8:1, and further preferably 4.8-5.2:1.
[0017] In the present invention, controlling the concentration of NaF in the roughening solution to be 3-6 g / L and the concentration of HF in the roughening solution to be 1-3 mol / L is to adjust the reaction rate and roughening effect of the roughening process, remove impurities and oxides on the powder surface, and improve the bonding strength between the powder and the subsequent coating; if the concentration of NaF is too high and the concentration of HF is too low, it will cause over-corrosion or uneven corrosion on the powder surface, and may also increase problems such as the alkalinity of the solution. If the concentration of NaF is too low and the concentration of HF is too high, it will cause problems such as serious corrosion pits or corrosion stripes on the powder surface.
[0018] In the present invention, when sensitization + activation is carried out, the liquid-solid ratio here is the mass ratio of liquid to solid.
[0019] When applied industrially, sensitization and activation treatments can be carried out synchronously at room temperature. That is, at room temperature, the roughened hafnium cyanide powder is added to the treatment solution; under the action of ultrasonic waves, it is treated for 12-18 min, left to stand until the powder settles, and then rinsed with deionized water at least 2 times.
[0020] In the present invention, the pre-treated and dried hafnium cyanide powder is first added to the reducing solution to provide an environment conducive to the reduction of silver ions. Formaldehyde in the reducing agent can reduce silver ions to metallic silver, thereby forming a coating on the powder surface. Then, the silver solution is slowly added to control the concentration and reduction rate of silver ions, so that silver ions are evenly distributed in the reducing solution and react more smoothly with the reducing agent, which is conducive to the formation of a continuous and uniform coating. In industrial applications, the stability of silver during the reaction can be ensured and the formation of silver nodules at active sites can be avoided by stirring during the reaction and replenishing silver ions, so that the coating is as uniform as possible.
[0021] In the present invention, the silver solution is composed of silver nitrate and ammonia water; the reducing solution is composed of formaldehyde, ethanol and water.
[0022] In the present invention, the silver solution and the reducing solution constitute an electroless silver plating solution.
[0023] Preferably, the volume ratio of the silver solution to the reducing solution is silver solution: reducing solution = 1:1.02 - 1.08;
[0024] The silver solution is prepared according to the ratio of 8 g of silver nitrate to 80 ml of deionized water and 20 ml of ammonia water, and the concentration of the ammonia water is 25 - 28 wt%;
[0025] The reducing solution is prepared according to the ratio of 2 ml of formaldehyde to 95 ml of ethanol and 8 ml of deionized water.
[0026] In the present invention, a liquid environment with a majority of ethanol is used to dilute the concentration of formaldehyde, thereby slowing down the reduction rate of silver ions, while improving the stability of the solution and preventing precipitation or agglomeration during the silver plating process. Too little ethanol will cause the reduction rate of silver ions to be too fast, resulting in uneven coatings, agglomeration or spots and other problems.
[0027] In the present invention, during electroless plating, a rotation speed of 750 r / min - 1000 r / min, preferably 950 - 1000 r / min, is used to make the plating solution more evenly distributed on the powder surface and enhance the renewal of the plating solution; too low a rotation speed will cause uneven coating thickness, slow down the gas escape speed, and affect the quality and performance of the coating.
[0028] Through process optimization, the present invention for the first time obtains a uniform silver coating on the surface of HfC x N y powder; it can improve the oxidation resistance of HfC x N y powder and its wettability with the metal matrix, and obtain a uniform silver shell on its surface, realizing HfC x N y~Ag core-shell structure. At the same time, the present invention also realizes for the first time the uniform coating of a large proportion of silver layer on the surface of HfC x N y ceramic particles, which provides the necessary conditions for expanding the uses of HfC x N y ceramics. The process of the present invention is simple, with a high deposition rate, and has broad application prospects and important economic value. Description of the Drawings
[0029] Figure 1 is the macroscopic image of the hafnium cyanide raw powder and the powder after electroless silver plating in Example 6.
[0030] Figure 2 is the SEM image and EDS line scan diagram of the cross section of the Ag / Hf(C,N) composite powder in Example 6.
[0031] Figure 3 is the SEM image and EDS energy spectrum diagram of the hafnium cyanide powder after electroless silver plating in Example 1.
[0032] Figure 4 is the SEM image and EDS energy spectrum diagram of the hafnium cyanide powder after electroless silver plating in Example 2.
[0033] Figure 5 is the SEM image of the hafnium cyanide powder after electroless silver plating in Example 3.
[0034] Figure 6 is the SEM image and EDS energy spectrum diagram of the hafnium cyanide powder after electroless silver plating in Example 4.
[0035] Figure 7 is the SEM image and EDS energy spectrum diagram of the hafnium cyanide powder after electroless silver plating in Example 5.
[0036] Figure 8 is the SEM image and EDS energy spectrum diagram of the hafnium cyanide powder before and after electroless silver plating in Example 6.
[0037] Figure 9 is the EDS energy spectrum diagram of the silver-plated hafnium cyanide composite particles obtained in Comparative Example 1.
[0038] Figure 10 is the EDS energy spectrum diagram of the silver-plated hafnium cyanide composite particles obtained in Comparative Example 2.
[0039] Figure 11 is the EDS energy spectrum diagram of the silver-plated hafnium cyanide composite particles obtained in Comparative Example 3.
[0040] Figure 12 is the EDS energy spectrum diagram of the silver-plated hafnium cyanide composite particles obtained in Comparative Example 4.
[0041] It can be seen from Figure 1 that after silver plating, the color of the HfC x N y powder has changed significantly, from brownish - red to black - gray, indicating that the powder has undergone a violent reaction in the plating solution.
[0042] It can be seen from Figure 2 that in the coating, the Hf content is relatively high, and Ag particles are evenly distributed on the surface of the Hf(C,N) powder. However, due to the small particle size of the Ag particles, the proportion content is small. According to the compositional changes of Ag and Hf, the white surface layer in this study was regarded as the Ag - plated layer.
[0043] It can be seen from Figures 3 - 7 that a relatively high temperature will cause the self - decomposition of silver elements, too slow stirring speed will cause the agglomeration of silver particles, and too low silver content will result in uneven distribution of silver particles on the hafnium cyanide powder.
[0044] It can be seen from Figure 8 that after electroless plating of hafnium cyanide, the surface is composed of countless tiny silver particles piled up, and the silver particles are arranged closely and evenly distributed on the HfC x N y powder.
[0045] It can be seen from Figures 9 - 12 that in the coating obtained from the comparative example, the Ag content is not high, and the degree of covering the ceramic surface is not high. Specific Embodiments
[0046] Example 1
[0047] The surface of the hafnium cyanide powder was pretreated, and the specific method is as follows:
[0048] (a) Roughening: Add 10 g of hafnium cyanide powder (particle size 8 - 10 microns) to the roughening solution, and ultrasonically treat it at room temperature for 15 min. After standing until the powder settles, wash the powder 3 times with deionized water.
[0049] (b) Sensitization and activation: At room temperature, pour 200 ml of the sensitization and activation solution into the roughened hafnium cyanide powder. React under ultrasonic wave for 15 min, and after standing until the powder settles, rinse it 3 times with deionized water.
[0050] The preparation processes of the roughening solution and the activation and sensitization solution are as follows:
[0051] Roughening solution: Dissolve 0.4 g of NaF in 100 ml of deionized water, add 4 ml of HF with a concentration of about 40% to the completely dissolved solution, and stir evenly to obtain the roughening solution.
[0052] Sensitizing and activating solution: 0.5 g of PbCl2 was added to 12 ml of 37% concentrated HCl and stirred until dissolved. Then, deionized water was added to make the volume up to 20 ml, obtaining Solution 1. 32 g of NaCl was dissolved in 100 ml of deionized water to obtain Solution 2. Solution 1 and Solution 2 were mixed and stirred evenly to obtain Solution 3. 6 g of SnCl·2H2O was dissolved in 60 ml of deionized water, and while stirring, it was added to Solution 3. Finally, deionized water was added to make the volume up to 200 ml to obtain a dark green sensitizing and activating solution.
[0053] For electroless silver plating on hafnium cyanide powder, the specific method is as follows: The pretreated and dried hafnium cyanide powder was added to 100 ml of reducing solution. Then, 100 ml of silver solution was slowly poured into the reducing solution while stirring evenly with a glass rod to obtain an electroless plating solution. The electroless plating solution was placed in an ultrasonic water bath and stirred. The water bath temperature was 50 °C, the stirring speed was 750 r / min, and the stirring time was 90 min. The pH of electroless silver plating was 11. After that, the powder was washed, filtered, and dried to finally obtain silver-plated hafnium cyanide composite particles.
[0054] The preparation processes of the silver solution and the reducing solution are as follows:
[0055] Silver solution: At room temperature, 5 g of silver nitrate was fully dissolved in 80 ml of deionized water, and then 20 ml of ammonia water was added. The solution was continuously stirred with a glass rod. The solution first became turbid and then clarified to obtain the silver solution. The concentration of the ammonia water was 25 wt% (i.e., commercially available ammonia water).
[0056] Reducing solution: 2 ml of formaldehyde and 95 ml of ethanol were measured with a measuring cylinder and added to a beaker and stirred evenly. 8 ml of deionized water was poured into the mixture to obtain the reducing solution.
[0057] The microscopic morphology of the obtained coating is as Figure 3 shown, in which the proportion of Ag element is about 41.3 wt%.
[0058] Example 2:
[0059] The surface of hafnium cyanide powder was pretreated, and the specific method is as follows:
[0060] (a) Roughening: 10 g of hafnium cyanide powder (particle size 8 - 10 microns) was added to the roughening solution and ultrasonically treated at room temperature for 15 min. After standing until the powder settled, the powder was washed 3 times with deionized water.
[0061] (b) Sensitizing and activating: At room temperature, 200 ml of sensitizing and activating solution was poured into the roughened hafnium cyanide powder. The reaction was carried out for 15 min under ultrasonic wave action. After standing until the powder settled, it was rinsed 3 times with deionized water.
[0062] The preparation processes of the roughening solution and the activation and sensitization solution are as follows:
[0063] Roughening solution: Dissolve 0.4 g of NaF in 100 ml of deionized water. Add 4 ml of HF with a concentration of about 40% to the completely dissolved solution and stir evenly to obtain the roughening solution.
[0064] Activation and sensitization solution: Add 0.5 g of PbCl2 to 12 ml of 37% concentrated HCl and stir to dissolve. Then add deionized water to make up to 20 ml to obtain Solution 1. Dissolve 32 g of NaCl in 100 ml of deionized water to obtain Solution 2. Mix Solution 1 and Solution 2 and stir evenly to obtain Solution 3. Dissolve 6 g of SnCl·2H2O in 60 ml of deionized water and add it to Solution 3 while stirring. Finally, add deionized water to make up to 200 ml to obtain a dark green activation and sensitization solution.
[0065] For electroless silver plating on hafnium cyanide powder, the specific method is as follows: Add the pretreated and dried hafnium cyanide powder to 100 ml of the reducing solution. Then slowly pour 100 ml of the silver solution into the reducing solution and stir evenly with a glass rod to obtain the electroless plating solution. Place the electroless plating solution in an ultrasonic water bath and stir. The water bath temperature is 40 °C, the stirring speed is 750 r / min, the stirring time is 90 min, and the pH of electroless silver plating is 11. Then wash, filter, and dry the powder to finally obtain silver-plated hafnium cyanide composite particles.
[0066] The preparation processes of the silver solution and the reducing solution are as follows:
[0067] Silver solution: At room temperature, weigh 5 g of silver nitrate and dissolve it fully in 80 ml of deionized water. Then add 20 ml of ammonia water and continuously stir the solution with a glass rod. The solution first becomes turbid and then clear to obtain the silver solution. The concentration of the ammonia water is 25 wt% (i.e., commercially available ammonia water).
[0068] Reducing solution: Measure 2 ml of formaldehyde and 95 ml of ethanol with a measuring cylinder and add them to a beaker and stir evenly. Pour 8 ml of deionized water into the mixture to obtain the reducing solution.
[0069] The microscopic morphology of the obtained coating is as Figure 4 shown, in which the proportion of Ag element is about 67.2 wt%. Comparing Figure 3 , Figure 4 with the EDS spectra in, it can be seen that the Ag peak of the product obtained in Example 2 is significantly stronger than that of the product obtained in Example 1 at this time. At the same time, the intensity of the Hf peak of the product obtained in Example 2 decreases significantly, which proves to a certain extent that the uniformity of the coating in Example 2 is better than that in Example 1, and the thickness of the coating in Example 2 is also greater than that of the coating in Example 1.
[0070] Example 3:
[0071] The surface of hafnium cyanide powder is pretreated, and the specific method is as follows:
[0072] (a) Roughening: Add 10 g of hafnium cyanide powder (particle size 8 - 10 microns) into the roughening solution, and ultrasonicate at room temperature for 15 min. After standing until the powder settles, wash the powder with deionized water 3 times.
[0073] (b) Sensitization and activation: At room temperature, pour 200 ml of sensitization and activation solution into the roughened hafnium cyanide powder. React under ultrasonic wave for 15 min, and after standing until the powder settles, rinse it with deionized water 3 times.
[0074] The preparation processes of the roughening solution and the sensitization and activation solution are as follows:
[0075] Roughening solution: Dissolve 0.4 g of NaF in 100 ml of deionized water, add 4 ml of HF with a concentration of about 40% to the completely dissolved solution, and stir evenly to obtain the roughening solution.
[0076] Sensitization and activation solution: Add 0.5 g of PbCl2 to 12 ml of 37% concentrated HCl and stir to dissolve, then add deionized water to 20 ml to obtain Solution 1. Dissolve 32 g of NaCl in 100 ml of deionized water to obtain Solution 2. Mix Solution 1 and Solution 2 and stir evenly to obtain Solution 3. Dissolve 6 g of SnCl·2H2O in 60 ml of deionized water, and while stirring, add it to Solution 3, and finally add deionized water to 200 ml to obtain a dark green sensitization and activation solution.
[0077] For electroless silver plating on hafnium cyanide powder, the specific method is as follows: Add the pretreated and dried hafnium cyanide powder into 100 ml of reducing solution, then slowly pour 100 ml of silver solution into the reducing solution, and stir evenly with a glass rod to obtain the electroless plating solution. Place the electroless plating solution in an ultrasonic water bath and stir. The water bath temperature is 35 °C, the stirring speed is 750 r / min, the stirring time is 90 min, and the pH of electroless silver plating is 11. Then wash, filter, and dry the powder to finally obtain silver-plated hafnium cyanide composite particles.
[0078] The preparation processes of the silver solution and the reducing solution are as follows:
[0079] Silver solution: At room temperature, weigh 5 g of silver nitrate and dissolve it fully in 80 ml of deionized water, then add 20 ml of ammonia water, and continuously stir the solution with a glass rod. The solution first becomes turbid and then becomes clear to obtain the silver solution. The concentration of the ammonia water is 25 wt% (i.e., commercially available ammonia water).
[0080] Reducing solution: Measure 2 ml of formaldehyde and 95 ml of ethanol with a measuring cylinder and add them to a beaker, then stir evenly. Pour 8 ml of deionized water into the mixture to obtain the reducing solution.
[0081] The microscopic morphology of the obtained coating is as Figure 5 shown, where the proportion of Ag element is about 75.6 wt%.
[0082] Comparing Figure 3 and Figure 5 the EDS spectra in, it can be seen that the Ag peak of the product obtained in Example 3 is significantly stronger than that of the product obtained in Example 1 at this time. At the same time, the intensity of the Hf peak of the product obtained in Example 3 decreases significantly, which proves to a certain extent that the coating uniformity of Example 3 is better than that of Example 1, and the coating thickness of Example 3 is also greater than that of the coating layer in Example 1.
[0083] Example 4:
[0084] Perform pretreatment on the surface of hafnium cyanide powder, and the specific method is as follows:
[0085] (a) Roughening: Add 10 g of hafnium cyanide powder (particle size 8 - 10 microns) to the roughening solution, and ultrasonically treat it for 15 min at room temperature. After standing until the powder settles, wash the powder 3 times with deionized water.
[0086] (b) Sensitization and activation: At room temperature, pour 200 ml of sensitization and activation solution into the roughened hafnium cyanide powder. React under ultrasonic action for 15 min, and after standing until the powder settles, rinse it 3 times with deionized water.
[0087] The preparation processes of the roughening solution and the sensitization and activation solution are as follows:
[0088] Roughening solution: Dissolve 0.4 g of NaF in 100 ml of deionized water, add 4 ml of HF with a concentration of about 40% to the completely dissolved solution, and stir evenly to obtain the roughening solution.
[0089] Sensitization and activation solution: Dissolve 0.5 g of PbCl2 in 12 ml of 37% concentrated HCl and stir to dissolve, then add deionized water to 20 ml to obtain Solution 1. Dissolve 32 g of NaCl in 100 ml of deionized water to obtain Solution 2. Mix Solution 1 and Solution 2 and stir evenly to obtain Solution 3. Dissolve 6 g of SnCl·2H2O in 60 ml of deionized water, and while stirring, add it to Solution 3, and finally add deionized water to 200 ml to obtain a dark green sensitization and activation solution.
[0090] Electroless plating of hafnium cyanide powder with silver is carried out as follows: The pretreated and dried hafnium cyanide powder is added to 100 ml of the reducing solution, and then 100 ml of the silver solution is slowly poured into the reducing solution while stirring evenly with a glass rod to obtain the electroless plating solution. The electroless plating solution is placed in an ultrasonic water bath and stirred. The water bath temperature is 30 °C, the stirring speed is 750 r / min, the stirring time is 90 min, and the pH of the electroless silver plating is 11. Then, the powder is washed, filtered, and dried to finally obtain silver-plated hafnium cyanide composite particles.
[0091] The preparation processes of the silver solution and the reducing solution are as follows:
[0092] Silver solution: At room temperature, 5 g of silver nitrate is weighed and fully dissolved in 80 ml of deionized water, and then 20 ml of ammonia water is added. The solution is continuously stirred with a glass rod until it first becomes turbid and then clear to obtain the silver solution. The concentration of the ammonia water is 25 wt% (i.e., commercially available ammonia water).
[0093] Reducing solution: Measure 2 ml of formaldehyde and 95 ml of ethanol with a measuring cylinder and add them to a beaker, and stir evenly. Then pour 8 ml of deionized water into the mixture to obtain the reducing solution.
[0094] The microscopic morphology of the obtained coating is as Figure 6 shown, in which the proportion of Ag element is about 78.7 wt%.
[0095] Example 5:
[0096] Pretreatment is carried out on the surface of hafnium cyanide powder as follows:
[0097] (a) Roughening: Add 10 g of hafnium cyanide powder (particle size of 8 - 10 microns) to the roughening solution and ultrasonically treat it at room temperature for 15 min. After standing until the powder settles, wash the powder 3 times with deionized water.
[0098] (b) Sensitization and activation: At room temperature, pour 200 ml of the sensitization and activation solution into the roughened hafnium cyanide powder. React under ultrasonic wave for 15 min, and after standing until the powder settles, rinse it 3 times with deionized water.
[0099] The preparation processes of the roughening solution and the sensitization and activation solution are as follows:
[0100] Roughening solution: Dissolve 0.4 g of NaF in 100 ml of deionized water, and add 4 ml of HF with a concentration of about 40% to the completely dissolved solution, and stir evenly to obtain the roughening solution.
[0101] Sensitizing and activating solution: 0.5 g of PbCl2 was added to 12 ml of 37% concentrated HCl and stirred until dissolved. Then, deionized water was added to make the volume up to 20 ml, obtaining Solution 1. 32 g of NaCl was dissolved in 100 ml of deionized water to obtain Solution 2. Solution 1 and Solution 2 were mixed and stirred evenly to obtain Solution 3. 6 g of SnCl·2H2O was dissolved in 60 ml of deionized water, and while stirring, it was added to Solution 3. Finally, deionized water was added to make the volume up to 200 ml, obtaining a dark green sensitizing and activating solution.
[0102] For electroless silver plating on hafnium cyanide powder, the method is as follows: The pretreated and dried hafnium cyanide powder was added to 100 ml of the reducing solution. Then, 100 ml of the silver solution was slowly poured into the reducing solution, and at the same time, it was stirred evenly with a glass rod to obtain the electroless plating solution. The electroless plating solution was placed in an ultrasonic water bath and stirred. The water bath temperature was 30 °C, the stirring speed was 1000 r / min, and the stirring time was 90 min. The pH of the electroless silver plating was 11. After that, the powder was washed, filtered, and dried to finally obtain silver-plated hafnium cyanide composite particles.
[0103] The preparation processes of the silver solution and the reducing solution are as follows:
[0104] Silver solution: At room temperature, 5 g of silver nitrate was fully dissolved in 80 ml of deionized water. Then, 20 ml of ammonia water was added, and the solution was continuously stirred with a glass rod until it became turbid first and then clear to obtain the silver solution. The concentration of the ammonia water was 25 wt% (i.e., commercially available ammonia water).
[0105] Reducing solution: 2 ml of formaldehyde and 95 ml of ethanol were measured with a graduated cylinder and added to a beaker and stirred evenly. 8 ml of deionized water was poured into the mixture to obtain the reducing solution.
[0106] The microscopic morphology of the obtained coating is as Figure 7 shown, and the proportion of Ag element is about 83.7 wt%.
[0107] Example 6:
[0108] The surface of hafnium cyanide powder was pretreated, and the method is as follows:
[0109] (a) Roughening: 10 g of hafnium cyanide powder (particle size 8 - 10 microns) was added to the roughening solution and ultrasonically treated at room temperature for 15 min. After standing until the powder settled, the powder was washed 3 times with deionized water.
[0110] (b) Sensitizing and activating: At room temperature, 200 ml of the sensitizing and activating solution was poured into the roughened hafnium cyanide powder. Under the action of ultrasonic waves, the reaction was carried out for 15 min. After standing until the powder settled, it was rinsed 3 times with deionized water.
[0111] The preparation processes of the roughening solution and the activation sensitization solution are as follows:
[0112] Roughening solution: Dissolve 0.4 g of NaF in 100 ml of deionized water. Add 4 ml of HF with a concentration of about 40% to the completely dissolved solution, and stir evenly to obtain the roughening solution.
[0113] Activation sensitization solution: Add 0.5 g of PbCl2 to 12 ml of 37% concentrated HCl and stir to dissolve. Then add deionized water to make up to 20 ml to obtain Solution 1. Dissolve 32 g of NaCl in 100 ml of deionized water to obtain Solution 2. Mix Solution 1 and Solution 2 and stir evenly to obtain Solution 3. Dissolve 6 g of SnCl·2H2O in 60 ml of deionized water, and while stirring, add it to Solution 3. Finally, add deionized water to make up to 200 ml to obtain a dark green activation sensitization solution.
[0114] For electroless silver plating on hafnium cyanide powder, the specific method is as follows: Add the pretreated and dried hafnium cyanide powder to 100 ml of the reducing solution. Then slowly pour 100 ml of the silver solution into the reducing solution, and stir evenly with a glass rod to obtain the electroless plating solution. Place the electroless plating solution in an ultrasonic water bath and stir. The water bath temperature is 30 °C, the stirring speed is 1000 r / min, the stirring time is 90 min, and the pH of electroless silver plating is 11. Then wash, filter, and dry the powder to finally obtain silver-plated hafnium cyanide composite particles.
[0115] The preparation processes of the silver solution and the reducing solution are as follows:
[0116] Silver solution: At room temperature, weigh 8 g of silver nitrate and dissolve it fully in 80 ml of deionized water. Then add 20 ml of ammonia water, and continuously stir the solution with a glass rod. The solution first becomes turbid and then clear to obtain the silver solution. The concentration of the ammonia water is 25 wt% (i.e., commercially available ammonia water).
[0117] Reducing solution: Measure 2 ml of formaldehyde and 95 ml of ethanol with a measuring cylinder and add them to a beaker, and stir evenly. Pour 8 ml of deionized water into the mixture to obtain the reducing solution. The microscopic morphology of the obtained coating is as Figure 8 shown, with the Ag content as high as 88.2 wt% and evenly covering the Hf(C,N) particles.
[0118] Comparison Figures 3 - 8It can be seen from the EDS energy spectrum that the Ag peak of the product obtained in Example 6 is significantly stronger than that of the products obtained in other examples. At the same time, the intensity of the Hf peak of the product obtained in Example 6 is significantly reduced, which proves to a certain extent that the uniformity and integrity of the coating in Example 6 are better than those in Examples 1-5. At the same time, the coating thickness of Example 6 is also greater than that of the coating layers in Examples 1-5.
[0119] Comparative Example 1:
[0120] Compared with Example 6, the water bath temperature was set to 60°C, and the remaining methods and steps were the same as those in this article. The chemical silver plating effect was as follows: Figure 9 As shown, the Ag element accounts for about 15.8 At%.
[0121] Comparative Example 2:
[0122] The other conditions are exactly the same as those in Example 6, except that the roughening solution is hydrochloric acid, and the chemical silver plating effect is as follows: Figure 10 As shown, the Ag element accounts for about 18.7 At%.
[0123] Comparative Example 3
[0124] The other conditions are exactly the same as those in Example 6, except that the roughening solution is prepared by dissolving 0.1 g of NaF in 100 ml of deionized water, adding 0.4 ml of HF with a concentration of about 40% to the completely dissolved solution, and stirring evenly to obtain the roughening solution. Figure 11 As shown, the Ag element accounts for about 15.8 At%.
[0125] Comparative Example 4
[0126] Other conditions are exactly the same as those in Example 6, except that:
[0127] Reducing solution: 2 ml of formaldehyde and 95 ml of ethanol are measured with a measuring cylinder and added to a beaker, and stirred evenly. 100 ml of deionized water is poured into the mixed solution to obtain a reducing solution. The composition of the silver solution is consistent with that of Example 6. This results in that after uniform mixing, the amount of ethanol used in the chemical plating solution is less than the amount of water used.
[0128] Its chemical silver plating effect is as follows Figure 12 As shown, the Ag element accounts for about 29.2 At%, and the uniformity of the coating is far worse than that of Example 6.
[0129] Conclusion: Through the comparison, it can be seen that HfC x N y Too high powder silver plating temperature, too low silver source AgNO3 concentration and too slow stirring speed will affect the final plating effect. Therefore, choosing appropriate process conditions is very important for ultra-high temperature HfCx N y Electroless silver plating on the powder surface is very crucial.
Claims
1. A preparation method for electroless silver plating on the surface of hafnium cyanide powder; characterized by It includes the following steps: 1) Pretreatment: The raw material powder is coarsened, sensitized + activated, and dried in sequence; the raw material powder is hafnium cyanide powder, and the chemical formula of the hafnium cyanide powder is: HfC x N y ; The roughening is as follows: adding hafnium cyanide powder into the roughening solution, ultrasonically treating at room temperature, then standing until the powder settles, and then washing with deionized water; the roughening solution is composed of NaF and HF, where the concentration of NaF is 3-6 g / L, and in the roughening solution, the concentration of HF is 1-3 mol / L; The sensitization + activation is as follows: adding the roughened hafnium cyanide powder into the treatment solution; synchronously performing sensitization and activation treatment under ultrasonic wave action for at least 10 min, standing until the powder settles, and rinsing with deionized water; the treatment solution is composed of PbCl2, HCl, SnCl, and NaCl; where the concentration of PbCl2 is 0.4-0.6 g / L, the concentration of HCl is 0.5-1.0 mol / L, the concentration of SnCl·2H2O is 25-35 g / L, and the concentration of NaCl is 150-170 g / L; 2) Electroless plating: adding the pretreated and dried hafnium cyanide powder into the reducing solution, and then adding the silver-containing solution into the reducing solution, stirring evenly to obtain the electroless silver plating solution; at a temperature of 30°C - 50°C, preferably 30 - 40°C, stirring the electroless plating solution for electroless plating, after the electroless plating is completed, washing, filtering, and drying the powder to obtain silver-plated hafnium cyanide composite particles; in the electroless silver plating solution, the concentration of silver nitrate AgNO3 is 25-40 g / L, the concentration of ammonia water is 2.5-3.5 mol / L, the concentration of formaldehyde HCHO is 0.3-0.35 mol / L, and the concentration of ethanol is 10-11.5 mol / L; and the amount of ethanol used in the electroless silver plating solution is greater than the amount of water used; the pH of the electroless silver plating solution is 11-12; During electroless plating, the stirring speed is 750 r / min - 1000 r / min.
2. The preparation method of electroless silver plating on the surface of hafnium cyanide powder according to claim 1, characterized in that: The particle size of the raw material powder is 8-10 microns.
3. The preparation method of electroless silver plating on the surface of hafnium cyanide powder according to claim 1, characterized in that: During roughening, adding hafnium cyanide powder into the roughening solution, ultrasonically treating at room temperature for 10-20 min, then standing until the powder settles, and washing the powder with deionized water at least 2 times; in the roughening solution, the concentration of NaF is 3.5-4.5 g / L, and the concentration of HF is 1.5-2.5 mol / L.
4. A preparation method for electroless silver plating on the surface of hafnium cyanide powder according to claim 3, characterized in that: During roughening, the liquid-solid ratio is greater than or equal to 4:1, preferably 4-8:1, and further preferably 4.8-5.2:
1.
5. The preparation method of electroless silver plating on the surface of hafnium cyanide powder according to claim 1, characterized in that: During sensitization and activation, the liquid-solid ratio is greater than or equal to 4:1, preferably 4-8:1, and further preferably 4.8-5.2:1, and the liquid-solid ratio here is the mass ratio of the liquid to the solid.
6. The preparation method of electroless silver plating on the surface of hafnium cyanide powder according to claim 1, characterized in that: At room temperature, adding the roughened hafnium cyanide powder into the treatment solution; treating under ultrasonic wave action for 12-18 min, standing until the powder settles, and rinsing with deionized water at least 2 times.
7. A method for preparing electroless silver plating on the surface of hafnium cyanide powder according to claim 1, characterized in that: The silver solution is composed of silver nitrate and ammonia water; the reducing solution is composed of formaldehyde, ethanol, and water; The silver solution and the reducing solution form the electroless silver plating solution.
8. A method for preparing electroless silver plating on the surface of hafnium cyanide powder according to claim 7, characterized in that: The silver solution and the reducing solution are in a volume ratio of silver solution:reducing solution = 1:1.02 to 1.08; The silver solution is prepared according to the ratio of 8 g of silver nitrate to 80 ml of deionized water and 20 ml of ammonia water, and the concentration of the ammonia water is 25 to 28 wt%; The reducing solution is prepared according to the ratio of 2 ml of formaldehyde to 95 ml of ethanol and 8 ml of deionized water.
9. The preparation method of electroless silver plating on the surface of hafnium cyanide powder according to claim 1, characterized in that: During electroless plating, stirring is carried out at a rotation speed of 950 r / min to 1000 r / min.
Citation Information
Patent Citations
Steady multitime supplementary fiber chemical silver coating method
CN101012552A